Identification of honey bee plant sources to support the planning of apiculture locations in Sibolangit Natural Tourism Park - Dwi Endah Widyasuti; Sri Meliana Saragih (Global Forest Journal, 2025)
Sibolangit Natural Tourism Park (SNTP) is a forest with an essential ecologicalfunction and is considered a conservation area. SNTP is currently trying toincrease the benefits of the forest through non-timber forest products, namely,honey bee cultivation. This study aimed to identify the type of plant source of beefeed plants in SNTP. The methods utilized are literature studies and observationalstudies using two radius points, namely radius one and radius two, at a 500-meterseparation. Based on the results of a literature study, it was found that 56 speciesof bee food sources in SNTP, including 36 plant species, of which the floweringperiod has been identified, namely 19 species of flowering plants throughout theyear and 17 flowering seasonally. Based on the point one observation radiusresults, 25 species of bee feed plants were obtained, with the dominant plant beingCoffea arabica. A radius of two through 10 types of bee feed plants was obtainedat the observation point. The dominating plants are Arenga pinnata, Arengaobtusifolia, and Coffea arabica. Observation of radius one shows a more diversevariety of plants than radius two. The diversity of bee food plants in SNTPsupports the honey bee cultivation